Design, Synthesis and Antimycobacterial Activity of Novel Imidazo[1,2-a]pyridine Amide-Cinnamamide Hybrids - Linhu Li; Zhuorong Li; Mingliang Liu; Weiyi Shen; Bin Wang; Huiyuan Guo; Yu Lu (Molecules, 2015)
We report herein the design and synthesis of a series of novel imidazo[1,2-a]pyridine amide-cinnamamide hybrids linked via an alkyl carbon chain. All 38 new hybrids were evaluated for their antimycobacterial activity against M. tuberculosis (MTB) H37Rv ATCC 27294 using the microplate Alamar Blue assay (MABA). Although the hybrids are less active than the two reference compounds, the promising activity (MICs: 4 μg/mL) of 2,6-dimethylimidazo[1,2-a]pyridine amide-cinnamamide hybrids 11e and 11k could be a good starting point to further find new lead compounds against multi-drug-resistant tuberculosis.